Code-Switching in EFL Classrooms: Typology and Communicative Roles - Darong, Hieronimus Canggung; Guna, Stanislaus (FKIP Universitas Lampung, 2023)
Code-Switching in EFL Classrooms: Typology and Communicative Roles. The purpose of this study was to look into the types and functions of code-switching that are used in an EFL teacher classroom interactions. The teacher’s interactions in this qualitative study were observed, recorded and subsequently transcribed. A multi-step analytical procedure that included data reduction, data visualization, and drawing/verifying findings was carried out. The findings showed that the teacher used three different types of as well as six functions of code-switching during interactions in the classroom. The types include tag switching (12), intra-sentential switching (37), and inter-sentential switching (62). Besides, the researcher found that the code-switching used by the teacher has the referential function (2), the directive function (31), the expressive function (20), the phatic function (18), the metalinguistic function (26) times, and poetic function (3). In conclusion, the use of code-switching in class interactions can help students’ comprehension and engagement in English language learning while considering the students level. Keywords: code-switching, function, type, interactionDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202310